O-175 Impact of female chromosomal polymorphic variants on ovarian reserve markers and fertility treatments prognosis. (6th August 2021) - Luque, L; Ruíz, N; Linares, Á; Bartolomé, J; Ortíz, J A; Fabregat, A; García-Hernández, E; Ten, J; Bernabéu, R
Abstract: Study question: Could the presence of chromosomal polymorphisms in women undergoing fertility treatments influence ovarian reserve, oocyte preservation or IVF clinical outcomes? Summary answer: Polymorphic variants of chromosomes seem to adversely influence the Anti-Müllerian Hormone (AMH) serum levels and the post-thawing oocyte survival rate. What is known already: Infertile couples have been reported to have a higher incidence of karyotype abnormalities than the general population, which could lead to lower fertility rates. However, few studies have demonstrated the controversial relationship between these karyotype alterations in women and the specific involvement of these variants and their combinations in an IVF cycle. Therefore, there is a growing interest in categorizing chromosomal polymorphic variants and relating them to the subsequent evolution in ART cycles. Study design, size, duration: Retrospective evaluation of a cohort of women undergoing IVF cycles in a private fertility center. The sample included 280 cycles performed between July 2017 and December 2020. The study explored the correlation between karyotype polymorphisms and IVF outcomes in terms of: Anti-Müllerian Hormone (AMH) level, Antral Follicle Count (AFC), Oocyte Maturity (MII), Oocyte Survival after Thawing (TS), Fertilization (FZ), Useful Embryos (UE), Biochemical (BP) and Clinical Pregnancy (CP), Miscarriage (M) and Live Birth (LB) rates. Participants/materials, setting, methods: Women with karyotype performed before an IVF cycle. Chromosome analysis was carried out according to the International System for Human Cytogenetic Nomenclature guidelines (ISCN). Only own eggs cycles were included, and testicular sperm cycles were excluded. The normality of the distribution of the variables was assessed using the Shapiro-Wilk test. The association between IVF cycle parameters and the presence of polymorphisms was assessed by T-Student (parametric) or U-Mann-Whitney (non-parametric). Main results and the role of chance: From a total of 280 IVF cycles, 198 met the inclusion criteria: Control Group (CG) with normal karyotype (94) and Study Group (SG) with presence of polymorphisms (104) were analyzed. Cycles with fresh (136) and warmed (62) oocytes were included. Mean female age was 37.66 ± 3.99 (CG) and 36.61 ± 3.72 (SG). The overall outcome rates were: 75.82% MII, 81.39% TS, 72.78% FZ, 49.07% UE on day 5, 21.82% BP, 78.18% CP, 14.53% M and 63.65% LB. Statistically significant differences were found between the presence of polymorphisms and mean AMH serum level between CG (2.36 ng/mL) and SG (1.74 ng/mL) (p = 0.04), especially when the type "qh+" was detected (1.01 ng/mL) (p = 0.02). Furthermore, statistically significant differences were found regarding oocyte thawing survival rate, which decreased in the SG (78.94%) compared to the CG (93.69%) (p = 0.02), mainly when the type "ps+" was detected (75.13%) (p < 0.01). No statistically significant differences were found between the presence of polymorphism and the AFC (p = 0.25), MII (p = 0.10), FZ (p = 0.93) or UE (p = 0.52) rate on day 5. In the same way, from 106 embryo transfers (ET) performed, no significant differences were found for BP, CP, M and LB rates (p > 0.05). Limitations, reasons for caution: Larger prospective studies including homogeneous cohorts are needed in order to corroborate our initial results. Wider implications of the findings: Our findings may represent a practical tool in order to advise these patients about their reproductive success, especially, in terms of post-thawing oocyte survival prognosis. Therefore, it could be provided more personalized prognostic information before embarking on IVF treatments. Trial registration number: Not Applicable